The combination of lenalidomide and dexamethasone reduces bone resorption in responding patients with relapsed/refractory multiple myeloma but has no effect on bone formation: Final results on 205 patients of the Greek myeloma study group - Terpos, E.; Christoulas, D.; Kastritis, E.; Katodritou, E.; Papatheodorou, A.; Pouli, A.; Kyrtsonis, M.-C.; Michalis, E.; Papanikolaou, X.; Gkotzamanidou, M.; Koulieris, E.; Gavriatopoulou, M.; et al. (American Journal of Hematology, 2014)
The combination of lenalidomide plus dexamethasone (RD) is very effective for patients with relapsed/refractory myeloma. However, the effect of RD on bone metabolism has not been previously evaluated in these patients. To address this issue, we initially performed a retrospective study in 106 consecutive patients with relapsed or refractory myeloma who received RD. We measured the following bone indices on Cycle 1/Day 1 and then on Cycles 3 and 6/Day 28: dickkopf-1 (Dkk-1), sRANKL, osteoprotegerin (OPG), bone resorption markers (C-telopeptide of collagen type-I, CTX and TRACP-5b) and bone formation markers (bone-specific alkaline phosphatase-bALP and osteocalcin). RD produced a reduction of CTX only in responders, with no effect on bone formation. To validate these results, we then evaluated prospectively 99 patients who received either RD (n=50) or VRD (bortezomib + RD, n=49). RD reduced CTX, mainly in responders but showed no effect on bone formation, confirming the result of the retrospective study. However, the addition of bortezomib to RD (VRD arm) reduced Dkk-1, sRANKL/OPG, and CTX, while it increased bALP and OC after six cycles of therapy. These changes were irrespective of treatment response, which was similar between treatment arms. No skeletal-related events were observed in the VRD arm while two, nonresponding patients treated with RD developed a vertebral fracture. We conclude that RD reduces bone resorption only in responding patients with relapsed/refractory myeloma but has no effect on bone formation. Combination with bortezomib, which enhances bone formation, seems to be preferred for the management of myeloma patients with osteolytic disease. © 2013 Wiley Periodicals, Inc.